IDENTIFYING AND QUANTIFYING URBAN RECHARGE: A REVIEW - Lerner D.N. (My University, 2002)
The sources of and pathways for groundwater recharge in urban areas are more numerous and complex than in rural environments. Buildings, roads, and other surface infrastructure combine with man-made drainage networks to change the pathways for precipitation. Some direct recharge is lost, but additional recharge can occur from storm drainage systems. Large amounts of water are imported into most cities for supply, distributed through underground pipes, and collected again in sewers or septic tanks. The leaks from these pipe networks often provide substantial recharge. Sources of recharge in urban areas are identified through piezometry, chemical signatures, and water balances. All three approaches have problems. Recharge is quantified either by individual components (direct recharge, water-mains leakage, septic tanks, etc.) or holistically. Working with individual components requires large amounts of data, much of which is uncertain and is likely to lead to large uncertainties in the final result. Recommended holistic approaches include the use of groundwater modelling and solute balances, where various types of data are integrated. Urban recharge remains an under-researched topic, with few high-quality case studies reported in the literature.
Keywords: GROUNDWATER RECHARGE; URBAN GROUNDWATER; RAINFALL/RUNOFF; UNSATURATED ZONE; GENERAL HYDROGEOLOGY